2021
DOI: 10.1021/acsami.0c17744
|View full text |Cite
|
Sign up to set email alerts
|

Antifouling Antioxidant Zwitterionic Dextran Hydrogels as Wound Dressing Materials with Excellent Healing Activities

Abstract: Hydrogels as wound dressings have received great attention in recent years. It is highly important yet challenging to develop hydrogel dressings that are biocompatible and that can promote wound healing by lowering the risk of inflammatory responses. In this work, we designed and prepared zwitterionic dextran-based hydrogels using carboxybetaine dextran (CB-Dex) and sulfobetaine dextran (SB-Dex) as raw materials, respectively. The efficacy of CB-Dex and SB-Dex hydrogels in promoting wound recovery was evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 40 publications
0
51
0
Order By: Relevance
“…For example, Wei et al reported two zwitterionic dextran hydrogels (CB-Dex and SB-Dex). 122 Their research work confirmed that zwitterionic modified dextran can minimize bacterial adhesion, prevent wound infection, and accelerate wound healing. In addition, Lv and Wei et al 123 recently developed an anti-swelling conductive hydrogel (DN-FT-HCl) with high toughness, high compressive modulus, and high ionic conductivity, and developed an underwater strain sensor based on this hydrogel.…”
Section: Other Polymersmentioning
confidence: 88%
“…For example, Wei et al reported two zwitterionic dextran hydrogels (CB-Dex and SB-Dex). 122 Their research work confirmed that zwitterionic modified dextran can minimize bacterial adhesion, prevent wound infection, and accelerate wound healing. In addition, Lv and Wei et al 123 recently developed an anti-swelling conductive hydrogel (DN-FT-HCl) with high toughness, high compressive modulus, and high ionic conductivity, and developed an underwater strain sensor based on this hydrogel.…”
Section: Other Polymersmentioning
confidence: 88%
“…For better wound healing effects, the corporation of zwitterionic hydrogel and assistant factors such as growth factors, antimicrobial agents, and antioxidants are widely used in recent wound healing research. Qiu et al [ 172 ] modified dextran with SB unit or CB unit and then formed SB-Dextran and CB-Dextran hydrogel with the borax crosslinker. The anomeric hydrogens of α-D-glucopyranose can be attacked by free radicals easily, which provide dextran scavenging capacity against the hydroxyl radical.…”
Section: Biomedical Applications Of Zwitterionic Hydrogelsmentioning
confidence: 99%
“…Dextran has a large number of pendant hydroxyl groups and can be easily modified. Dextran-based hydrogels have been shown to significantly promote cardiovascular formation and skin regeneration in vivo (Qiu et al, 2021;Guan et al, 2021). Recently, polyphenols structurally similar to the adhesion proteins secreted by marine mussels have been shown to have strong adhesion to various substrates (Lee et al, 2007), especially by enhancing the cell adhesion and proliferation (Han et al, 2015).…”
Section: Introductionmentioning
confidence: 99%